2010
DOI: 10.2147/jpr.s9445
|View full text |Cite
|
Sign up to set email alerts
|

Postdural puncture headache and pregabalin

Abstract: Background:Even if carried out under optimal conditions, postdural puncture headache is still a frustrating and unpleasant complication in spinal anesthesia. This syndrome has an estimated incidence from less than 1% to about 5% of patients undergoing spinal anesthesia, even in the highest risk subset, the young, female, and pregnant population.Case presentation:In our two female cases, headaches started following spinal anesthesia on the 11th and 14th hours, respectively. No response was obtained from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…One controlled trial found that sumatriptan was ineffective in treatment of PDPH 64 . There are also reports regarding successful use of adrenocorticotropic hormone (ACTH), mirtazapine, pregabalin, and trials of gabapentin, methergine, with metoclopramide and hydrocortisone in treatment of PDPH 65‐73 . Gupta et al reported complete relief in 40 of 48 patients after injection of 60 U of ACTH intramuscularly 65 .…”
Section: Approach To Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…One controlled trial found that sumatriptan was ineffective in treatment of PDPH 64 . There are also reports regarding successful use of adrenocorticotropic hormone (ACTH), mirtazapine, pregabalin, and trials of gabapentin, methergine, with metoclopramide and hydrocortisone in treatment of PDPH 65‐73 . Gupta et al reported complete relief in 40 of 48 patients after injection of 60 U of ACTH intramuscularly 65 .…”
Section: Approach To Treatmentmentioning
confidence: 99%
“…The patients in the treatment group had significantly lower pain analog scores ( P < .05) over the course of all 4 days and reported essentially no pain on days 3 and 4 of treatment. Zencirci et al reported 2 patients who improved on pregabalin 50 mg every 8 hours over a course of 3 days 72 . Hakim et al administered oral methergine 0.25 mg 3 times a day and 10 mg of oral metoclorpramide twice a day for 48 hours to 25 obstetric patients with complete resolution of symptoms in 24 of 25 patients by day 3 73 .…”
Section: Approach To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The first spinal anesthesia was carried out by Dr August Bier in 1899 and his anesthetic technique has become the standard practice for lower extremity and abdominal surgery worldwide [1]. Nowadays, the most commonly used drugs for spinal anesthesia are local anesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…It develops in 16% to 86% of the cases after attempted spinal block with large bore needles [2]. It is described as frontal or occipital pressure occurring in the upright position and decreasing or resolving when supine [3]. According to the International Tension Headache Society, the criteria for PDPH include a tension headache that develops less than seven days after a spinal puncture, occurs or worsens less than fifteen minutes after assuming the upright position, and improves less than thirty minutes in the recumbent position with at least one of the following symptoms: neck stiffness, tinnitus, hypacusia, photophobia, and nausea.…”
Section: Introductionmentioning
confidence: 99%